Dental caries and associated factors among diabetic and nondiabetic adult patients attending Bichena Primary Hospital’s Outpatient Department - Shiferaw, Anley; Alem, Girma; Tsehay, Mekonnen; Kibret, Getiye Dejenu (Frontiers in Oral Health, 2022)
Purpose Dental caries is a significant public health issue affecting both the diabetic and nondiabetic populations. However, the problem and associated factors of dental caries among diabetics and nondiabetics patients are not well-known in Ethiopia. This study aims to compare the prevalence of dental caries and associated factors among diabetic and nondiabetic patients at the Outpatient Department of Bichena Primary Hospital in Northwest, Ethiopia. Methods Institutional based, comparative cross-sectional study was conducted from October 7 to December 6, 2019, among 200 diabetes and 400 nondiabetic adult patients. A consecutive sampling technique was implemented to recruit study participants. Data were collected by a pretested structured questionnaire and analysis was performed in Statistical Package for Social Science version 20. Bivariable and multivariable logistic regressions were employed and variables with a p-value < 0.05 were declared statistically significant. Results A total of 582 patients were involved in the study with a response rate of 97.0%. The prevalence of dental caries was 67.9% [95% confidence interval (CI): 63.2%–72.8%] and 79.6% (95% CI: 74.0%–85.70%) in nondiabetic and diabetic group, respectively. Females gender [adjusted odds ratio (AOR) = 1.79, 95% CI: 1.15–2.77], poor oral hygiene (AOR = 2.95, 95% CI: 1.71–5.11), lack of regular teeth cleaning habits (AOR = 3.26, 95% CI: 2.13–4.97), feeling dry mouth (AOR = 2.31, 95% CI: 1.11–4.81), sugared tea drinking (AOR = 2.00, 95% CI: 1.18–3.38), inadequate oral health knowledge (AOR = 3.51, 95% CI: 2.19–5.62), and khat chewing (AOR = 2.14, 95% CI: 1.24–3.71) were significantly associated factors with high prevalence of dental caries. Conclusion The prevalence of caries was significantly higher among diabetics than nondiabetics. Oral health education with preventive measures such as improving teeth cleaning practice, reducing sugary foods and drinks intake, and improving oral hygiene practice of patients should be mainstreamed along with diabetic follow-up care.